Self-regulation predicts companionship in children with autism. (2nd November 2022) - Nuske, Heather J.; Shih, Wendy I.; Sparapani, Nicole; Baczewski, Lauren; Dimachkie Nunnally, Amanda; Hochheimer, Samantha; Garcia, Consuelo; Castellon, Fernanda; Levato, Lynne; Fischer, Erin; Atkinson-Diaz, Zabryna L.; Li, Jennica; et al.
Abstract: Self-regulation is associated with many positive outcomes in children with and without autism, including increased mental health and academic achievement, and decreased problem behavior. Less is known regarding whether and how self-regulation and symptoms of mental health challenges (internalizing and externalizing problems) relate to social outcomes, such as friendship quality and loneliness. Parents and teachers of 106 children with autism aged 5–12 reported on children's self-regulation difficulties and externalizing and internalizing symptoms. Four-to-five months later, children reported on the quality of their friendship with their best friend (companionship, conflict, helpfulness, sense of relationship security, closeness), and their feelings of loneliness. Linear regression was used to examine the effects of self-regulation and symptoms of mental health challenges on friendship quality and loneliness. Less self-regulation difficulties predicted stronger companionship and girls had better quality friendships with their best friend than did boys, in terms of companionship, helpfulness, security and closeness, confirming that they have a protective advantage in friendship development. Autism symptoms, IQ, and age were not associated with friendship quality or loneliness. Results highlight the importance of self-regulation and mental health interventions for school-aged children with autism.